Empowering Through Energy: A Renewable Energy-Based Model of Community Empowerment in Agrarian Villages of Aceh Tamiang - Rahmad Purnama; Zulfahmi Zulfahmi; Firmansyah Firmansyah; Rini Febrianti; Maya Maria; Heriani Heriani (Electronic Journal of Education, Social Economics and Technology, 2026)
Inequality in access to renewable energy presents a significant challenge to achieving sustainable development in agrarian villages throughout Indonesia. This research investigates the dynamics of community empowerment in the uptake of renewable energy within rural agricultural contexts, specifically focusing on Aceh Tamiang Regency. Utilizing a grounded theory methodology, the study operates within the framework of critical constructivism, positing that energy is not solely a technological instrument, but a socio-cultural construct influenced by local knowledge, governance, and collaborative institutional frameworks. The research methodology encompasses a range of qualitative approaches, including in-depth interviews, focus group discussions, participatory observations, and document analysis, engaging various stakeholders such as farmers, village officials, extension workers, and institutions. The analysis employed open coding, axial coding, and selective coding techniques, resulting in a conceptual model reflecting three interconnected pillars: (1) energy literacy and community empowerment, (2) adaptive village governance aligned with the Sustainable Development Goals (SDGs), and (3) multi-stakeholder institutional synergy. Key findings indicate that the effectiveness of renewable energy initiatives hinges not only on technological advancements and financial resources but also on essential collective values such as cooperation, social learning, and trust within the community. In extending Zimmerman’s empowerment framework, this study incorporates local cultural dimensions, enriching Geels’ socio-technical systems theory by emphasizing moral and spiritual influences and enhancing Rhodes' network governance theory through the integration of trust and social capital. This research contributes to the discourse on energy transition by offering a bottom-up, socially grounded theoretical model that reconceptualizes renewable energy as both a catalyst for rural empowerment and a mechanism for socio-institutional transformation. It highlights that the path towards sustainable energy development in rural areas necessitates a harmonious interplay of community engagement, inclusive governance, and cooperative institutions. Consequently, energy emerges not merely as an economic asset but as a vital social force promoting justice, dignity, and resilience in agrarian lifestyles.